Tác động của danh tiếng đến trách nhiệm xã hội doanh nghiệp và ý định mua hàng của khách hàng trong ngành sữa Việt Nam - Phạm Xuân Lan; Nguyễn Ngọc Hiền (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
This study proposes a model that examines the relationships among reputation, trust, corporate social responsibility, and consumer purchase intention. Specifically, by using a sample of 383 consumers of baby milk powder, the study considers the impact of reputation on consumer perception of corporate social responsibility, as well as the mediating role of consumer trust and purchase intention regarded as the final result. The results indicate that corporate reputation has a positive, direct impact on perceived social responsibility. Furthermore, the effect is found to be partially mediated by consumer trust, cultivated and nourished by reputation, which allows consumers to perceive corporate social responsibility in a positive manner. Finally, as also shown in the study, trust and social responsibility impact positively on consumers’ purchase intention.